Students’ understanding of ecology: Identifying interaction between ecosystem components - Puti Siswandari; Farhah Nadhif Tsalist; Sinta Atsmari Khomsah; Nazwa Noor Hidayah; Risa Meidawati (Biosfer: Jurnal Pendidikan Biologi, 2026)
Ecology learning in schools should go beyond explaining isolated concepts, involving visual representations to help students comprehend the complexity of ecological systems. This study aimed to analyze high school students’ understanding of the interactions among ecosystem components using student-generated drawings. Sixty-three 10th-grade students participated in the study. This study employed a pre-test and post-test design by collecting student-generated drawings at two time points: before the instructional intervention to establish a baseline and after the intervention to assess its impact on students’ understanding. The students’ drawings of river ecosystems were analyzed and coded on three system levels: biotic-abiotic (BA), micro-macro (MM), and components-mechanisms-phenomena (CMP). Results from the Wilcoxon Signed-Rank Test indicated significant improvements in students’ ability to represent interactions across these system levels. Effect size calculations revealed large effects between BA:MM and BA:CMP, suggesting substantial learning gains. A moderate effect was observed between MM:CMP. While students showed a clear improvement in describing BA:MM interactions, their depictions of CMP remained limited. These findings highlight the importance of teaching strategies on ecosystem that explicitly integrate abiotic mechanisms at multiple biological scales. Such approaches can support students in visualizing ecological processes as interconnected systems, rather than fragmented components.